Rivaroxaban with or without Aspirin in Stable Cardiovascular Disease - Eikelboom, John W; Connolly, Stuart J; Bosch, Jackie; Dagenais, Gilles R; Hart, Robert G; Shestakovska, Olga; Diaz, Rafael; Alings, Marco; Lonn, Eva M; Anand, Sonia S; Widimsky, Petr; Hori, Masatsugu; et al. (The New England journal of medicine, 2017)
In patients with stable cardiovascular disease, those receiving rivaroxaban plus aspirin had fewer major cardiovascular events but more major bleeding events than those receiving aspirin alone. Rivaroxaban alone did not result in fewer major cardiovascular events than aspirin alone.